Chromophobe Renal Cell Carcinoma with Sarcomatoid Differentiation (Journal of Kidney Cancer, 2023)
Chromophobe renal cell carcinoma (chRCC) is one of the less common types of kidney cancer and generally portends a more favorable prognosis. RCC with sarcomatoid differentiation has a more aggressive clinical course with poor outcomes. Four cases of chRCC with varying degrees of sarcomatoid differentiation were retrospectively reviewed at our institution, and clinicopathologic data as well as clinical courses were reported. Patients with higher degrees of sarcomatoid differentiation and larger tumors at presentation generally had and worse overall survival. chRCC with sarcomatoid differentiation portends a poor prognosis with limited data on systemic treatment options for metastatic disease.